2015
DOI: 10.1038/mi.2014.120
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 restrains neutrophil granule serine protease function and regulates the innate immune response during Klebsiella pneumoniae infection

Abstract: Neutrophil elastase (NE) and cathepsin G (CG) contribute to intracellular microbial killing but, if left unchecked and released extracellularly, promotes tissue damage. Conversely, mechanisms that constrain neutrophil serine protease activity protect against tissue damage but may have the untoward effect of disabling the microbial killing arsenal. The host elaborates thrombospondin-1 (TSP-1), a matricellular protein released during inflammation, but its role during neutrophil activation following microbial pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…Further, because host cells recognize and internalize M. catarrhalis through integrin a5b1-associated fibronectin in an opsonin-independent manner, the inhibition of phagocytosis could also be due to a blockade of M. catarrhalis-fibronectin-integrin association by the competitive binding of COMP to fibronectin and integrins (15,48). Interestingly, another thrombospondin family member, thrombospondin-1, which is localized in the epithelial layer of skin, blood, and myocardium, also inhibits phagocytosis of bacterial and fungal pathogens by neutrophils and macrophages in mouse models (49)(50)(51). Thrombospondin-1 restrains the activity of neutrophil elastase and enhances dissemination and infection of Klebsiella pneumoniae in mice (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, because host cells recognize and internalize M. catarrhalis through integrin a5b1-associated fibronectin in an opsonin-independent manner, the inhibition of phagocytosis could also be due to a blockade of M. catarrhalis-fibronectin-integrin association by the competitive binding of COMP to fibronectin and integrins (15,48). Interestingly, another thrombospondin family member, thrombospondin-1, which is localized in the epithelial layer of skin, blood, and myocardium, also inhibits phagocytosis of bacterial and fungal pathogens by neutrophils and macrophages in mouse models (49)(50)(51). Thrombospondin-1 restrains the activity of neutrophil elastase and enhances dissemination and infection of Klebsiella pneumoniae in mice (51).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, another thrombospondin family member, thrombospondin-1, which is localized in the epithelial layer of skin, blood, and myocardium, also inhibits phagocytosis of bacterial and fungal pathogens by neutrophils and macrophages in mouse models (49)(50)(51). Thrombospondin-1 restrains the activity of neutrophil elastase and enhances dissemination and infection of Klebsiella pneumoniae in mice (51). Based on similar structures of thrombospondin-1 and COMP, COMP may use a similar pattern to block phagocytic killing and, therefore, promote M. catarrhalis infection of the respiratory tracts.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to determine the contribution of this receptor to pulmonary host defense against the K2 strain, which is a well-known ATCC research strain that is pathogenic in mice [21]. At 24 and 48 hours following bacterial inoculation of 2 × 10 3 CFU, Cd36 −/− mice showed a higher bacterial burden in the lungs, compared with WT mice ( Figure 1A).…”
Section: Extrapulmonary Dissemination Following Intrapulmonary Infectmentioning
confidence: 99%
“…Initial studies indicated that the K. pneumoniae K2 strain grown to early logarithmic phase but not at the late logarithmic phase induced a reproducible pathogenic phenotype in the lungs of wild-type (WT) mice, and subsequent studies used an OD 600 nm of 0.2 to prepare the bacterial inoculum. We have previously described a detailed method of intratracheal administration of bacteria by direct visualization [21,23].…”
Section: Cd36mentioning
confidence: 99%
See 1 more Smart Citation